H2S / CO2 corrosion resistant ultralow-carbon low-chromium seamless line pipe and manufacturing method thereof
By strictly controlling element ratio and process flow, the prepared ultra-low carbon low-chromium seamless pipeline pipe solves the problem of insufficient corrosion resistance of CO2/H2S in the existing technology, achieves excellent corrosion resistance and high strength, and meets the needs of oil and gas conveying pipelines in the oil field.
Patent Information
- Application Number
- CN202411787915.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-25
AI Technical Summary
The corrosion-resistant seamless pipeline pipes prepared in the prior art have high carbon and chromium content and low weldability, and the corrosion resistance of CO2/H2S is difficult to meet practical applications.
Ultra-low carbon low-chromium seamless pipeline pipes are prepared by strictly controlling element ratios, especially Cr/Mo ratios, combined with electric furnace + refining + vacuum treatment + mold casting + forging, and ultra-low carbon low-chromium seamless pipelines have low Cr, low P, low S, low carbon equivalent Pcm and excellent corrosion resistance of CO2/H2S.
The prepared seamless pipeline pipe has good resistance to CO2 corrosion and H2S stress corrosion. It meets the production requirements of oil and gas conveying pipelines of oil field medium and has a strength of up to X65Q steel grade.
Smart Images

Figure BDA0005174564040000041 
Figure BDA0005174564040000051
Abstract
Description
Technical Field
[0001] The present invention relates to the field of seamless steel pipes, and more specifically to a H-resistant seamless steel pipe. 2 S / CO 2 Corrosion-resistant ultra-low carbon low chromium seamless line pipe and method of making the same. Background Art
[0002] At present, the seamless steel pipes used in the oil and gas industry are mainly divided into two types according to their uses: oil casing and transmission pipeline. 2 and H 2 S, the corrosion resistance of the material needs to be considered when selecting materials. In order to resist hydrogen sulfide and carbon dioxide corrosion, a certain amount of chromium is generally added to the material design to achieve the purpose of carbon dioxide corrosion resistance.
[0003] Chinese patent CN105648337A discloses a low-carbon anti-CO 2 Normalized seamless line pipe and manufacturing method thereof, smelting - ingot casting - forging or rolling - perforation - hot rolling - heat treatment (normalizing), the composition design of this patent has too high C element content, low Cr element content, lacks Cu, Ni, Mo and other elements, and cannot verify whether it meets the designed Pcm < 0.24.
[0004] Chinese patent CN102199736A discloses a high-strength, CO 2 / H 2 S-corrosion seamless gathering and transportation pipeline pipe, electric furnace or converter - continuous casting - Mannesman hot rolling - heat treatment (quenching and tempering or normalizing), the manufacturing process of this patent adopts Mannesman hot rolling, and the Mannesman continuous rolling unit belongs to a double-roller oblique rolling and piercing mill. Chinese patent CN106119727A discloses a high-strength and toughness 80Ksi or less resistant to CO 2 Corrosion seamless gathering and transportation line pipe and its manufacturing method, converter-continuous casting-continuous rolling-peeling-segmentation-cold centering-CPE unit rolling-heat treatment (normalizing + tempering), this patented smelting process is completed by converter, while the current domestic low alloy and alloy steel smelting has been gradually replaced by short-process and more environmentally friendly electric furnaces. In terms of raw materials, it saves more raw materials and costs than converter steelmaking.
[0005] Chinese patent CN102154593A discloses an X80 steel grade corrosion resistant low temperature seamless pipeline, which is electric furnace-refining-vacuum degassing-continuous casting-perforation-hot rolling-heat treatment (quenching and tempering). The carbon element ratio of this patent is 0.08-0.14%, which cannot meet the requirements of low carbon equivalent; the Cr element ratio is ≤0.15%, and the Cr content of this patent cannot meet the requirements of CO resistance. 2 Corrosion requirements: Mo element is equipped with 0.10~0.20%.
[0006] The corrosion-resistant seamless line pipes prepared by the prior art have high carbon and chromium contents, low weldability, and CO 2 / H 2 S's corrosion resistance is difficult to meet practical application requirements. Summary of the invention
[0007] The purpose of the present invention is to overcome the shortcomings of the prior art and provide an anti-H 2 S / CO 2 The invention relates to an ultra-low carbon and low chromium seamless pipeline and its manufacturing method. The ultra-low carbon and low chromium seamless pipeline is prepared by strictly controlling the element ratio, especially the Cr / Mo ratio, and combining the process of electric furnace + refining + vacuum treatment + die casting + forging to manufacture the steel billet. The ultra-low carbon and low chromium seamless pipeline has low Cr, low P, low S, low carbon equivalent Pcm and excellent CO resistance. 2 / H 2 S corrosive.
[0008] The technical solution adopted by the present invention to solve the technical problem is:
[0009] The present invention provides an anti-H 2 S / CO 2 The corroded ultra-low carbon low-chromium seamless pipeline has the following chemical compositions by mass percentage: C: 0.02-0.05%, Si: 0.17-0.35%, Mn: 0.45-0.55%, P≤0.015%, S≤0.003%, Ni≤0.20%, Cr: 2.9-3.1%, Mo: 0.25-0.35%, Cu≤0.20%, Al≤0.05%, V≤0.03%, Ca≤0.0040%, N≤0.0100%, O≤0.0030%, H≤0.0002%, B≤0.0005%, the rest are Fe and unavoidable impurities, and the Cr / Mo ratio is 10:1, and satisfies Pcm≤0.24, Pcm=C+Si / 30+Mn / 20+Cu / 20+Ni / 60+Cr / 20+Mo / 15+V / 10+5B.
[0010] Furthermore, the metallographic structure of the ultra-low carbon low chromium seamless pipeline is ultra-low carbon bainite, and the grain size is greater than grade 8.5.
[0011] Furthermore, the yield strength of the ultra-low carbon and low chromium seamless line pipe is 450-600 MPa, the tensile strength is 535-760 MPa, the elongation is greater than 20%, and the transverse impact energy at -10°C is greater than 250 J.
[0012] Furthermore, the ultra-low carbon and low chromium seamless pipeline has a specification of Φ60.3-457.2 mm×3.91-50 mm, a steel grade of X65Q, and a length of 10-12 meters.
[0013] In the formula design of the present invention, the role of each element is:
[0014] C is one of the main elements in carbon steel that improves the strength of steel grades, and is also the main element that affects the Pcm carbon equivalent. Therefore, C is designed to be 0.02-0.05%.
[0015] Si is one of the common elements in steel. The affinity of silicon to oxygen is second only to aluminum and titanium, and stronger than manganese, chromium and vanadium. Therefore, it is used as a reducing agent and deoxidizer in the steelmaking process, so it is generally not less than 0.1%; but if it is higher than 0.5%, it will affect the toughness and plasticity of the steel, so the design Si: 0.17~0.35%.
[0016] Mn is a good deoxidizer and desulfurizer. It can eliminate or weaken the hot brittleness of steel caused by sulfur, thereby improving the hot processing properties of steel. Manganese can refine pearlite and strongly increase the hardenability of steel. However, if the manganese content is too high, it tends to coarsen the grains and increase the temper brittleness sensitivity of steel; therefore, Mn is designed to be 0.45-0.55%.
[0017] P can cause serious segregation of steel and increase the temper brittleness sensitivity of steel. It is generally considered to be a harmful element, so P is designed to be ≤ 0.015%.
[0018] S is generally considered to be a harmful element remaining in steel, which is detrimental to corrosion resistance, toughness, etc., and is generally controlled below 0.003%.
[0019] Ni is the main alloying element for forming and stabilizing austenite, and its role in this regard is second only to carbon and nitrogen. It can improve the low-temperature toughness of steel and improve the hardenability of steel. However, this element is expensive and should not be added unless there is a special requirement for low-temperature use. Therefore, Ni is designed to be ≤0.20%.
[0020] Cr significantly improves the anti-oxidation effect of steel and increases the corrosion resistance of steel. In the present invention, it is used as the main anti-CO 2 It is generally believed that as the Cr content increases, the material's resistance to CO 2 The ability also increased significantly, but increased to about 13%, which would reduce the resistance to H 2 S stress corrosion resistance. This steel is designed to be an economical CO 2 Corrosion materials, reducing the chromium content makes it have a corrosion resistance compared to ordinary low-carbon microalloy steel, but if it is lower than 2.9%, the corrosion resistance will be greatly reduced; at the same time, if about 13% chromium is added to ordinary low-carbon steel, the steel structure is martensite, which will reduce the material's resistance to H 2 S stress corrosion ability, so reducing the chromium content will also improve the structure, thereby improving the material's resistance to H 2S stress corrosion resistance; in addition, too high Cr content will also increase the Pcm carbon equivalent, thereby reducing the weldability of the material. Therefore, Cr is designed to be 2.9~3.1%.
[0021] Mo exists in the solid solution phase and carbide phase in steel. It improves hardenability, improves heat resistance, prevents temper brittleness, and improves corrosion resistance and pitting resistance in certain media. Mo: 0.25-0.35%.
[0022] Cu, in steel, plays a prominent role in improving the atmospheric corrosion resistance of ordinary low alloy steel, especially when used in combination with phosphorus. It cannot be removed during the metallurgical process. When copper-containing scrap steel is repeatedly smelted, the residual copper content in it will accumulate more and more. Copper is one of the scarce metals and a strategic material. Therefore, it should not be intentionally added during smelting. Considering that Cu is also one of the factors affecting the Pcm carbon equivalent, this design Cu≤0.20%.
[0023] Al has a great affinity with oxygen and nitrogen. Its main function in steel is to deoxidize and nitrogenize, and refine grains. Therefore, this design Al: ≤0.05%.
[0024] V has a strong affinity with carbon, nitrogen and oxygen, and forms corresponding extremely stable compounds with them. Considering that it is also one of the factors affecting the carbon equivalent of Pcm, the present design V is ≤0.03%.
[0025] B, as a residual element, the lower the better.
[0026] The Cr / Mo ratio is 10:1, and Pcm≤0.24 is satisfied. The Cr / Mo ratio is higher than 10:1. In the prepared seamless pipeline, due to the relatively low carbon content, if the Mo content is relatively low, it will affect the heat treatment of the steel pipe and reduce the strength.
[0027] Another aspect of the present invention provides an anti-H 2 S / CO 2 The manufacturing method of the corroded ultra-low carbon low chromium seamless pipeline pipe is as follows:
[0028] The raw materials are subjected to electric arc furnace, secondary refining, vacuum treatment, and mold casting into steel ingots, and round billets are obtained by forging, with a forging ratio of 2 to 10. After forging, annealing and polishing are performed to obtain round billets, and a centering hole is punched at the head end of the round billet;
[0029] The round billet is heated to 1200-1280℃ in a ring furnace and then rolled into rolled steel pipe using a PQF piercing and rolling mill.
[0030] After the rolled steel pipe is water quenched at 900-950℃ and tempered at 600-700℃, it meets API SPEC5L46 TH X65Q steel grade performance requirements for H2 S / CO 2 Corroded ultra-low carbon low chromium seamless line pipe.
[0031] The advantages and positive effects of the present invention are:
[0032] The present invention strictly controls the ratio of each element, especially by simultaneously controlling Cr / Mo, Pcm≤0.24, and combines electric arc furnace + secondary refining + vacuum treatment, die casting, forging process, and the synergistic effect of the prepared seamless pipeline has good resistance to CO 2 Corrosion resistance, H resistance 2 S stress corrosion resistance. DETAILED DESCRIPTION
[0033] The present invention is further described in detail below through specific examples. The following examples are only illustrative and not restrictive, and the protection scope of the present invention cannot be limited thereto.
[0034] Example 1
[0035] An anti-H 2 S / CO 2 The corroded ultra-low carbon low chromium seamless pipeline (X65Q-3Cr) has the following chemical compositions by mass percentage: C: 0.03%, Si: 0.32%, Mn: 0.49%, P: 0.004%, S: 0.001%, Ni: 0.020%, Cr: 2.9%, Mo: 0.29%, Cu: 0.01%, Al: 0.025%, V: 0.03%, Ca: 0.0009%, N: ≤0.0100%, O: ≤0.0030%, H: ≤0.0002%, B: 0.0005%, the rest are Fe and unavoidable impurities, the Cr / Mo ratio is 10:1 and satisfies Pcm≤0.24, Pcm=C+Si / 30+Mn / 20+Cu / 20+Ni / 60+Cr / 20+Mo / 15+V / 10+5B.
[0036] According to the above composition, the steel pipe with the specification of 219.1mm×12.7mm, steel grade X65Q and length of 11 meters is manufactured. The production process is as follows: weigh the corresponding raw materials according to the element ratio, put them into a 30-ton electric furnace arc, use an electric arc furnace, secondary refining, vacuum treatment, die-cast into steel ingots, 3150t fast forging machine + 1800 fine forging machine forging materials, after forging, the forging ratio is 10, annealing, polishing to get a round billet, and a centering hole is punched at the head end of the round billet; the round billet is heated to a temperature of 1200℃ in a ring furnace and then rolled into a rolled steel pipe using a PQF perforated continuous rolling unit. After the rolled steel pipe is quenched at 900℃ and tempered at 600℃, it meets API SPEC 5L46 TH X65Q steel grade performance requirements for H 2 S / CO2 Corroded ultra-low carbon low chromium seamless line pipe (X65Q-3Cr).
[0037] Comparative Example 1
[0038] The only difference from Example 1 is that the element ratio is different from that in Example 1, the C content is 0.09%, and the Cr content is 0.08%.
[0039] Comparative Example 2
[0040] The only difference from Example 1 is that the element ratio is different from that in Example 1, the Mo content is 0.1%, and the Cr / Mo ratio is 30.
[0041] The mechanical properties of the seamless line pipes prepared in Example 1 and Comparative Examples 1-2 were tested, and the results are shown in Table 1.
[0042] Table 1 Mechanical properties test data of seamless line pipes prepared in Example 1 and Comparative Examples 1-2
[0043] Example Yield strength MPa Tensile strength MPa -10℃ Impact energy J Elongation A% Example 1 500 565 333 46 Comparative Example 1 445 500 295 29 Comparative Example 2 430 480 285 28
[0044] Anti-H 2 S / CO 2 Corrosion test conditions are shown in Table 2:
[0045] Table 2 Corrosion test under simulated working conditions
[0046] Test temperature <![CDATA[H 2 S partial pressure]]> <![CDATA[CO 2 Partial Pressure]]> <![CDATA[N 2 ]]> Total pressure Cl- concentration Speed pH 42℃ 0.08MPa 0.16MPa 4.26MPa 4.5MPa 40679mg / L 3m / s 7
[0047] The comparison of the corrosion test results of the embodiment and the comparative example is shown in Table 3:
[0048] Table 3 Corrosion test results of embodiments and comparative examples
[0049]
[0050]
[0051] The above experimental data were completed in a laboratory autoclave, and the solution is an aqueous solution, which cannot be equated with the corrosion rate in the oil, gas and water environment produced by the oil field. Generally speaking, if there is oil and gas, oil and water in the medium, the corrosion rate is lower than the corrosion rate in the laboratory. From the above data, it can be seen that under the same steel grade, the corrosion rate of the steel prepared in Example 1 of the present invention under simulated working conditions is lower than that of Comparative Examples 1-2. At the same time, the steel described in the present invention has passed the HIC test and four-point bending SSC test of API SPEC 5L-2018, and the test method implements NACE TM 0284-2016 and NACE TM 0177-2016.
[0052] The ultra-low carbon and low chromium seamless line pipe prepared in Example 1 of the present invention meets the requirements of oil fields. 2 S also contains CO 2 The production requirements of medium oil and gas transmission pipelines are that the strength can reach X65Q steel grade. The successful development of this steel grade is of great significance in the petroleum and petrochemical industry, and the present invention has a huge market prospect.
[0053] The above description is only a preferred embodiment of the present invention. It should be pointed out that a person skilled in the art can make several modifications and improvements without departing from the inventive concept, which all belong to the protection scope of the present invention.
Claims
1. An ultra-low carbon low chromium seamless line pipe resistant to H2S / CO2 corrosion, characterized in that: The mass percentage of its chemical composition is: C: 0.02-0.05%, Si: 0.17-0.35%, Mn: 0.45-0.55%, P≤0.015%, S≤0.003%, Ni≤0.20%, Cr: 2.9-3.1%, Mo: 0.25-0.35%, Cu≤0.20%, Al≤0.05%, V≤0.03%, Ca≤0.0040%, N≤0.0100%, O≤0.0030%, H≤0.0002%, B≤0.0005%, the rest are Fe and unavoidable impurities, and the Cr / Mo ratio is 10:1, and satisfies Pcm≤0.24, Pcm=C+Si / 30+Mn / 20+Cu / 20+Ni / 60+Cr / 20+Mo / 15+V / 10+5B.
2. The ultra-low carbon low chromium seamless line pipe according to claim 1, characterized in that: The metallographic structure of the ultra-low carbon low chromium seamless line pipe is ultra-low carbon bainite, and the grain size is greater than grade 8.
5.
3. The ultra-low carbon low chromium seamless line pipe according to claim 1, characterized in that: The ultra-low carbon and low chromium seamless pipeline has a yield strength of 450-600 MPa, a tensile strength of 535-760 MPa, an elongation greater than 20%, and a transverse impact energy greater than 250 J at -10°C.
4. The ultra-low carbon low chromium seamless line pipe according to claim 1, characterized in that: The ultra-low carbon and low chromium seamless pipeline has a specification of Φ60.3-457.2 mm×3.91-30 mm and a length of 10-12 meters.
5. The method for manufacturing an ultra-low carbon and low chromium seamless line pipe according to any one of claims 1 to 4, characterized in that: The production process is as follows: The raw materials are cast into steel ingots by electric arc furnace + secondary refining + vacuum treatment, and round billets are obtained by forging, with a forging ratio of 2 to 10. After forging, they are annealed and polished to obtain round billets, and a centering hole is punched at the head end of the round billet; then, they are heated to 1200 to 1280°C in a ring furnace and continuously rolled into rolled steel pipes; The rolled steel pipe is water quenched at 900-950°C and tempered at 600-700°C to obtain an ultra-low carbon and low chromium seamless line pipe.
Citation Information
Patent Citations
X80 steel grade anti-corrosion low-temperature seamless line pipe
CN102154593A
High-strength and anti-CO2 / H2S corrosion seamless gathering-line pipe
CN102199736A
Low-carbon CO2-resistant normalized seamless line pipe and manufacturing method thereof
CN105648337A
Seamless gathering pipeline tube with high toughness below 80 Ksi and carbon dioxide corrosion resistance, and manufacturing method thereof
CN106119727A